A skew and leptokurtic distribution with polynomial tails and characterizing functions in closed form - Matthias Fischer (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2012)
We introduce a new skewed and leptokurtic distribution derived from the hyperbolic secant distribution and Johnson's S transformation. Properties of this new distribution are given. Finally, we empirically demonstrate in the context of financial return data that its exibility is comparable to that of their most advanced peers.
Keywords: 330; hyperbolic secant distribution; SU-transformation; skewness; leptokurtosis; polynomial tails